PENERAPAN METODE DISCOVERY TERHADAP HASIL BELAJAR LARI JARAK PENDEK PADA SISWA KELAS X MAN 2 PRAYA - Ahmad Nurjani; Isyani Isyani (Universitas Pendidikan Mandalika, 2017)
The lack of interest of students in learning athletics, especially short distance running, is due to the teachers’ teaching methods that tend to be boring and less interesting explanation from the teacher, resulted in students less ability to know or master the techniques in doing short distance running. Therefore, teaching method is very important to the outcome of learning. The purpose of this study is to find out how the implementation of discovery method can improve the achievement of short distance running on students class X of MAN 2 Praya. As for the research design, it used the stages in the form of two cycles; each cycle consists of planning, implementation, observation and reflection. The population in use was the entire class X students of MAN 2 Praya and the sample was class X MAN 2 which amounted to 17 students. The sampling technique used the purposive sampling. The methods used to collect data in this research was the method of observation, documentation, and test while for the data analysis technique of learning result used critical value, whereas the data was analyzed by finding the mastery of individual learning and critical value. The assessment technique is classified to be successful if the critical value reached 85% of students who get a minimum score of 75% seen in the results of learning cycle I and cycle II. Based on the results of the assessment analysis in the first cycle, it was obtained that the percentage of critical value was 58.8% while on the second cycle the percentage of students' critical value was 82%. Then, it can be concluded that the discovery method can improve the achievement of short distance running on the students of class X of MAN 2 Praya in academic year 2016/2017.